Hox genes in the coordination of embryonic development. Model of hourglass in the description of vertebrate ontogenesis - Dolomatov, Sergey; Kazakova, Vera; Zukow, Walery (Journal of Education, Health and Sport, 2021)
The paper analyzes the role of HOX genes in the processes of embryonic development of vertebrates. Based on the analysis, it is concluded that HOX genes are the most important regulators of embryonic development. The HOX genes predominantly realize their influence through specific HOX proteins that have the ability to regulate the expression of target genes. The order of expression of the HOX genes, as a rule, obeys the rule of temporal and spatial colinearity. This mechanism determines the temporal and spatial course of tissue morphogenesis during embryonic development and tissue regeneration in organisms that have reached the stage of maturity. The process of embryo morphogenesis, determined by highly conserved HOX genes, explains the appearance of the phylotypic period - the stage of embryonic development of vertebrates, at which embryos of different classes of vertebrates have distinct morphological similarities.